Paradoxical Facilitation of Attention in Healthy Humans - Shirley Fecteau; Alvaro Pascual-Leone; Hugo Théoret (Behavioural Neurology)
Transcranial magnetic stimulation (TMS)-induced virtual lesions in healthy subjects can be used to test neurofunctional models of disease. The interhemispheric rivalry model of heminglect is well suited for such investigations, as simple predictions derived from clinical data can be tested without the caveats normally associated with lesion studies. One of these predictions is that release from contralateral inhibition should lead to increased parietal responsiveness, which, in turn, would enhance spatial attention. Here, we detail studies showing TMS-induced paradoxical functional facilitation of attention in healthy individuals and highlight their contribution to the understanding and treatment of neglect syndromes.